Floristic composition and turnover analysis in Dahomey Gap and the surrounding sub‐humid Togolese mountain minor forest refuges: Importance for biogeography and biodiversity conservation in sub‐Saharan Africa. Issue 10 (4th October 2022) - Adjossou, Kossi; Kokou, Kouami; Deconchat, Marc
Abstract: The origin of Dahomey Gap (DG) flora is one of the central biogeographical questions in sub‐Saharan, which has been addressed in several studies. However, floristic evidence based on representative samples from the DG seems to be lacking in the scientific debate. The present study was conducted to fill this gap. Specifically, we assessed Togolese mountain riparian forests as minor forest refugia, examined their contribution to larger sub‐Saharan forest refugia, and discussed the significance of these findings for biogeography and biodiversity conservation. Southwest Togo, West Africa, and sub‐Saharan Upper Guinea Region Floristic data were collected in riparian forests through an intensive botanical inventory ( n = 198; 50 × 10 m 2 ). A comparative analysis was performed based on the floristic evidence related to forest refuges. The results showed significantly high species richness (868 species) and a high gamma and beta diversity associated with spatial turnover patterns. They also showed a high affinity between the study forests and large sub‐Saharan forest refugia. Riparian forests share about 60% of their current species richness with large sub‐Saharan forest refugia and contained refuge bio‐indicator species. The floristic evidence, consistent with those of other studies, suggests that Togolese mountains would have very ancient origins and have experienced paleoclimatic events. The studied riparian would have served as refuges during recurrent climatic episodes. Our results support the minimal forest fragmentation hypothesis (network of refugia along rivers). However, they seem to be incompatible with the idea that the DG flora may be essentially a relic of the early Holocene. In sub‐Saharan Africa, where maintaining a vast area of natural forest is difficult due to human pressure, efforts to preserve maximum species diversity should include a focus on the conservation of minor forest refuges, particularly in sub‐humid mountain riparian zone. Abstract : The origin of the DG is one of the central biogeographical questions in sub‐Saharan Africa, which has been addressed in recent phylogenetic studies. Till date, no study based on large floristic data collected in the DG has addressed this question. Our work, based on large floristic data collected in the DG and compared with those of regional floras, is consistent with the recurrent opening of the DG and suggests that during the warm period, the riparian forests of the sub‐humid Togolese Mountains would have served as important minor forest refugia and would continue to play this role in the future climate change.